NOOSPHERE. NOOSPHERE DEVELOPMENT. NOOSPHERE EDUCATION - Natalia V. Maslova (Открытое образование (Москва))
It is offered the understanding of noosphere as environments of unity of the individual and collective inspired reason. It is certain that noosphere development is impossible without the noosphere transition called to produce scientific, psychological, world view, ideological, socially-technological, administrative transformations. Importance is shown semantic and valued updating in technologies of education, and also acmeological innovations. Conception of noosphere education as systems of theoretical, gnosiological, methodological, medical-psihological and practical looks is offered to nature of education and way of achievement of natural effect in education of rising generations. Principle of potential intellectual safety of educational technology is offered.